Inhibiting tumor necrosis factor‐alpha at time of induced intervertebral disc injury limits long‐term pain and degeneration in a rat model. Issue 2 (25th May 2018) - Evashwick‐Rogler, Thomas W.; Lai, Alon; Watanabe, Hironobu; Salandra, Jonathan M.; Winkelstein, Beth A.; Cho, Samuel K.; Hecht, Andrew C.; Iatridis, James C.
Abstract : To determine the role of tumor necrosis factor‐alpha (TNFα) on initiating painful intervertebral disc (IVD) degeneration, rat lumbar IVDs were punctured and injected with TNFα or anti‐TNFα, and the resulting pain behavior, IVD structural degeneration, and intradiscal pro‐inflammatory cytokine expressions were determined. TNFα injection increased pain and IVD degeneration, whereas anti‐TNFα decreased both pain and IVD degeneration to control levels, and pain was predicted by IVD degeneration and TNFα expression using a multivariate stepwise linear regression. We conclude TNFα is an initiator of painful IVD degeneration and its early inhibition can mitigate pain and degeneration. Abstract : Background: Painful intervertebral disc (IVD) degeneration has tremendous societal costs and few effective therapies. Intradiscal tumor necrosis factor‐alpha (TNFα) is commonly associated with low back pain, but the direct relationship remains unclear. Purpose: Treatment strategies for low back pain require improved understanding of the complex relationships between pain, intradiscal pro‐inflammatory cytokines, and structural IVD degeneration. A rat in vivo lumbar IVD puncture model was used to 1) determine the role of TNFα in initiating painful IVD degeneration, and 2) identify statistical relationships between painful behavior, IVD degeneration, and intradiscal pro‐inflammatory cytokine expression. Methods: Lumbar IVDs were punctured anteriorly and injected with TNFα, anti‐TNFα, or saline and compared with sham and naive controls. Hindpaw mechanical hyperalgesia was assayed weekly to determine pain over time. 6‐weeks post‐surgery, animals were sacrificed, and IVD degeneration, IVD height, and intradiscal TNFα and interleukin‐1 beta (IL‐1β) expressions were assayed. Results: Intradiscal TNFα injection increased pain and IVD degeneration whereas anti‐TNFα alleviated pain to sham level. Multivariate step‐wise linear regression identified pain threshold was predicted by IVD degeneration and intradiscal TNFα expression. Pain threshold was also linearly associated with IVD height loss and IL‐1β. Discussion: The significant associations between IVD degeneration, height loss, inflammation, and painful behavior highlight the multifactorial nature of painful IVD degeneration and the challenges to diagnose and treat a specific underlying factor. We concluded that TNFα is an initiator of painful IVD degeneration and its early inhibition can mitigate pain and degeneration. Intradiscal TNFα inhibition following IVD injury may warrant investigation for its potential to alter downstream painful IVD degeneration processes.